Thermal insulation composite material taking silicon dioxide hollow spheres as thermal insulation filler and preparation method of thermal insulation composite material

By growing hollow silica spheres in situ in the inorganic thermal insulation matrix, the problem of high thermal conductivity of inorganic thermal insulation materials is solved, efficient thermal insulation performance improvement and simplified preparation process, which is suitable for large-scale production.

CN119191813APending Publication Date: 2024-12-27ZHAOQING SANJIANG SILICON MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410950464.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-16
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing inorganic thermal insulation materials have high thermal conductivity, mainly because the large internal pores cannot completely suppress heat conduction and thermal convection, resulting in insufficient thermal insulation effect and complex preparation process.

Method used

Using hollow silica spheres as filler, a uniform emulsion is formed by alkoxysilane and aqueous surfactant solution. In situ growth technology is used to react the precursor of silica in the pores of the inorganic thermal insulation matrix to produce high-content dihydrogen Silicon oxide hollow spheres fill pores of the substrate to reduce thermal conductivity.

Benefits of technology

It effectively improves the thermal insulation performance, simplifies the preparation process, reduces costs, is suitable for large-scale production, and has huge application potential in the field of thermal insulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191813A_ABST
    Figure CN119191813A_ABST
Patent Text Reader

Abstract

The invention discloses a thermal insulation composite material as well as a preparation method and application thereof. The preparation method of the thermal insulation composite material provided by the invention comprises the following steps: enabling alkoxy silane and a surfactant aqueous solution to form a uniform emulsion, enabling an inorganic thermal insulation matrix to adsorb the emulsion, and removing a solvent after gelatinization to obtain the thermal insulation composite material, the surfactant aqueous solution is an aqueous solution containing a multi-block polyurethane surfactant and a cationic surfactant, and the volume concentration of the hollow microspheres in the emulsion is greater than or equal to 60%. The emulsion is mainly composed of silane precursor vesicle particles, has ultrahigh volume concentration, and is adsorbed by using an inorganic heat-insulating matrix, so that the vesicles form silicon dioxide hollow spheres in pores of the inorganic heat-insulating matrix, thereby obtaining the heat-insulating composite material taking the silicon dioxide hollow spheres as the heat-insulating filler. Compared with a conventional glass mat, the thermal insulation composite material has the advantage that the thermal conductivity is effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of thermal insulation materials, and more specifically relates to a thermal insulation composite material using hollow silicon dioxide balls as thermal insulation fillers. Background Art

[0002] With the rapid development of global society and economy, energy consumption continues to increase. Energy conservation and consumption reduction have become key issues in maintaining sustainable social development. Compared with adopting new energy technologies, improving the energy efficiency of existing facilities and reducing energy waste have greater potential and higher cost-effectiveness. Within the energy loss structure, heat transfer losses in building structures account for approximately 25% of total energy consumption. The development of new and efficient building insulation materials is of great significance in energy conservation and consumption reduction.

[0003] Traditional thermal insulation materials include organic insulation materials and inorganic insulation materials. Organic insulation materials include expanded polystyrene (EPS), extruded polystyrene (XPS), cellulose, polyurethane (PUR), etc., with thermal conductivity of 0.020~0.040W·m -1 ·K -1 Inorganic thermal insulation materials include mineral wool, refractory ceramics, expanded perlite (EP), etc., which have good fire resistance and durability, but there are hidden dangers in installation safety, easy to absorb moisture and high thermal conductivity.

[0004] The main reason for the high thermal conductivity of inorganic insulation materials is that the larger internal pores cannot completely suppress the heat transfer caused by heat conduction and heat convection. Finding a filler with stronger heat barrier ability and easy to process, and compounding it into the porous structure of traditional building insulation materials is an effective way to further enhance its thermal insulation performance.

[0005] Prior art discloses a thermal insulation felt using hollow silica as a filler. This method involves modifying the matrix and silica separately to impart oleophilic surfaces to both, improving the compatibility of the silica with the matrix and increasing the uniformity of the silica distribution within the matrix. However, this method is relatively complex to prepare, and the thermal insulation felt still suffers from insufficient thermal insulation performance. Summary of the Invention

[0006] In view of the shortcomings of the prior art, the primary purpose of the present invention is to provide a thermal insulation composite material with hollow silica spheres as filler.

[0007] Another object of the present invention is to provide a method for preparing the thermal insulation composite material.

[0008] Another object of the present invention is to provide a thermal insulation composite material prepared by the above preparation method.

[0009] Another object of the present invention is to provide applications of the thermal insulation composite material.

[0010] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0011] The present invention provides a method for preparing a thermal insulation composite material using hollow silica spheres as filler, comprising the following steps:

[0012] Alkoxysilane and a surfactant aqueous solution are made to form a uniform emulsion, the inorganic thermal insulation matrix is ​​made to absorb the emulsion, and the solvent is removed after gelation to obtain the thermal insulation composite material;

[0013] The surfactant aqueous solution is an aqueous solution containing a multi-block polyurethane surfactant and a cationic surfactant;

[0014] The volume concentration of the hollow microspheres in the emulsion is ≥60%.

[0015] In order to introduce the hollow silica sphere filler into the internal pores of the inorganic thermal insulation matrix, the present invention adopts an in-situ growth technology. The silica precursor is immersed in the pores of the inorganic thermal insulation matrix in an emulsion state, so that the silica precursor reacts inside the pores and the hollow silica spheres grow in situ inside the pores. In the emulsion of the present invention, the volume density of the hollow microspheres is extremely high. The volume of the emulsion does not shrink after drying in an open environment. Therefore, when the emulsion is immersed in the inorganic thermal insulation matrix for in-situ reaction, the generated hollow microspheres can fill the pores of the inorganic thermal insulation matrix to the maximum extent. The synthesized thermal insulation composite material has an extremely high content of hollow silica spheres, thereby effectively reducing thermal conductivity.

[0016] Preferably, the concentration of hollow microspheres in the emulsion is 100%.

[0017] Preferably, the alkoxysilane is selected from at least one of tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetrabutoxysilane, methyltrimethoxysilane, phenyltrimethoxysilane, octyltrimethoxysilane, methyltriethoxysilane, phenyltriethoxysilane and octyltriethoxysilane.

[0018] Preferably, the mass ratio of the alkoxysilane to the surfactant aqueous solution is 1-15:5-20. More preferably, the mass ratio of the alkoxysilane to the surfactant aqueous solution is 3-10:8-12.

[0019] Preferably, the method for preparing the surfactant aqueous solution comprises the following steps: dispersing the multi-block polyurethane surfactant and the cationic surfactant in water.

[0020] More preferably, the dispersion is carried out by stirring.

[0021] More preferably, the dispersion temperature is 15-60°C.

[0022] More preferably, the dispersion time is 0.5 to 2 hours.

[0023] The invention uses a multi-block polyurethane surfactant and a cationic surfactant as templates, and can make hollow silicon dioxide spheres form non-adhesive hollow microspheres at ultra-high concentrations.

[0024] Preferably, the preparation method of the multi-block polyurethane surfactant comprises the following steps:

[0025] The diisocyanate heated to 70-90° C. is reacted with an organic tin catalyst and a hydrophilic chain extender solution for 1-3 hours to obtain a primary reaction product; the primary reaction product is reacted with polyethylene glycol heated to 60-100° C. for 1-3 hours to obtain the multi-block polyurethane surfactant.

[0026] More preferably, the molar ratio of the diisocyanate, the hydrophilic chain extender, and the polyethylene glycol is 1:0.1-1.5:0.1-1.0;

[0027] More preferably, the diisocyanate is selected from at least one of dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, xylylene diisocyanate or methylcyclohexyl diisocyanate;

[0028] More preferably, the organotin catalyst is selected from at least one of dibutyltin dilaurate, stannous octoate, dibutyltin didodecylsulfide, or dibutyltin diacetate;

[0029] More preferably, the hydrophilic chain extender is selected from at least one of dimethylol propionic acid, dimethylol butyric acid, 1,2-propylene glycol-3-sulfonate sodium, 1,4-butanediol-2-sulfonate sodium, diethylenetriamine or methyldiethanolamine.

[0030] More preferably, the number average molecular weight of the polyethylene glycol is 600 g / mol to 3500 g / mol. More preferably, the polyethylene glycol is selected from at least one of PEG400, PEG600, PEG800, PEG1000, PEG1500 or PEG2000.

[0031] Preferably, the cationic surfactant is at least one selected from cetyltrimethylammonium bromide, dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, cetyltrimethylammonium chloride, sodium lauryl sulfate or sodium lauryl sulfonate.

[0032] Preferably, the pH of the surfactant aqueous solution is 3 to 9. More preferably, the pH of the surfactant aqueous solution is 5 to 8.

[0033] Preferably, the mass ratio of the multi-block polyurethane surfactant to the cationic surfactant in the surfactant aqueous solution is 5-15:0.5-3. More preferably, the mass ratio of the multi-block polyurethane surfactant to the cationic surfactant in the surfactant aqueous solution is 10-15:0.5-2.

[0034] Preferably, the mass ratio of the total amount of the multi-block polyurethane surfactant and the cationic surfactant in the surfactant aqueous solution to water is 20-40:100-450. More preferably, the mass ratio of the total amount of the multi-block polyurethane surfactant and the cationic surfactant in the surfactant aqueous solution to water is 30-35:150-400.

[0035] Preferably, the method of forming a uniform emulsion of the alkoxysilane and the surfactant aqueous solution comprises homogenization.

[0036] More preferably, the method of forming a uniform emulsion of the alkoxysilane and the surfactant aqueous solution further comprises stirring.

[0037] More preferably, the method of forming a uniform mixed solution of the alkoxysilane and the surfactant aqueous solution comprises sequentially performing homogenization and stirring.

[0038] More preferably, the homogenization speed is 5000-20000 rpm. More preferably, the homogenization speed is 8000-15000 rpm.

[0039] More preferably, the high-speed homogenization time is 1 to 30 minutes. More preferably, the high-speed homogenization time is 1 to 10 minutes.

[0040] More preferably, the stirring speed is 100-1000 rpm.

[0041] More preferably, the stirring time is 0 to 120 min. More preferably, the stirring time is 10 to 80 min.

[0042] More preferably, the stirring temperature is 10-80°C.

[0043] Preferably, the step of allowing the inorganic thermal insulation substrate to absorb the emulsion comprises: immersing the inorganic thermal insulation substrate in the emulsion. More preferably, after immersing the inorganic thermal insulation substrate in the emulsion, the inorganic thermal insulation substrate is taken out.

[0044] This invention cleverly utilizes the liquid nature of ungelled silica emulsion, allowing it to easily enter the tiny pores of the inorganic insulating matrix. Subsequent gelation allows hollow silica spheres to grow within the tiny voids of the inorganic insulating matrix, forming a thermal insulation composite material. In the resulting composite material, the hollow silica microspheres reduce the pore size of the inorganic insulating matrix, thereby reducing heat conduction and convection, effectively enhancing the thermal insulation capacity of the composite material.

[0045] Preferably, the gelation is carried out by standing.

[0046] Preferably, the gelation time is 12 to 72 hours.

[0047] Preferably, the gelation temperature is 20-80°C.

[0048] Preferably, the inorganic thermal insulation matrix is ​​selected from at least one of glass felt, rock wool or pre-oxidized fiber felt.

[0049] The present invention also provides a thermal insulation composite material prepared according to the above preparation method.

[0050] Preferably, the average particle size of the hollow silica spheres is 0.5 to 5 μm.

[0051] Preferably, the thermal conductivity of the thermal insulation composite material is 0.030-0.05 W / (m·K).

[0052] Preferably, the content of hollow silicon dioxide spheres in the thermal insulation composite material is 10 wt% to 30 wt%.

[0053] The present invention also provides the use of the above-mentioned thermal insulation composite material or the thermal insulation composite material prepared by the above-mentioned preparation method in the preparation of building thermal insulation and energy-saving materials, vehicle thermal insulation materials, new energy battery thermal insulation and fireproof materials, industrial pipeline insulation materials or chemical equipment thermal insulation materials.

[0054] Compared with the prior art, the present invention has the following beneficial effects:

[0055] The thermal insulation composite material prepared by the present invention, which uses hollow silica microspheres as the insulating filler, effectively improves the thermal insulation performance of the inorganic insulating matrix by in-situ growing the hollow silica microspheres within the voids of the inorganic insulating matrix. The thermal insulation performance of the thermal insulation composite material prepared by the present invention is superior to that of commercially available thermal insulation felt. The present invention has a simple preparation process, low cost, and is suitable for large-scale production, showing great potential for application in the field of thermal insulation. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 This is a macroscopic image of the thermal insulation composite material of Example 1;

[0057] Figure 2 1 is a side view of the thermal insulation composite material (left) and the glass fiber mat (right) of Example 1;

[0058] Figure 3 This is a SEM image of the thermal insulation composite material of Example 1;

[0059] Figure 4 This is a SEM image of the thermal insulation composite material of Example 2;

[0060] Figure 5 This is a SEM image of the thermal insulation composite material of Example 3;

[0061] Figure 6 This is the SEM image of the thermal insulation composite material of Example 4. DETAILED DESCRIPTION

[0062] Below in conjunction with specific embodiment, content of the present invention is further described, but embodiment does not limit the present invention in any form.If not otherwise specified, the technical means used in the embodiment are conventional means well known to those skilled in the art.Unless otherwise specified, the reagent, method and equipment used in the present embodiment are conventional reagents, methods and equipment in the art.

[0063] Unless otherwise specified, the multi-block polyurethane surfactants in the following examples and comparative examples were prepared by the following method: an N,N-dimethylformamide solution containing 44.5 g of isophorone diisocyanate was heated to 80° C., 0.1 g of dibutyltin dilaurate was added, and then an N,N-dimethylformamide solution containing 14.8 g of 2,2-dihydroxymethylbutyric acid was slowly added. After the addition was complete, the reaction was allowed to react for 2 h. The reaction product was added to 150 g of polyethylene glycol (number average molecular weight of 1000 g / mol) heated to 80° C., the reaction was carried out for 2 h, and the solvent was removed by vacuum to obtain a segmented polyurethane surfactant.

[0064] Fiberglass felt: size is 15cm long × 15cm wide × 5mm thick, Langfang Dongding Insulation Materials Co., Ltd.

[0065] Pre-oxidized silk felt: size is 15cm long × 15cm wide × 5mm thick, Shandong Haike Environmental Protection Materials Co., Ltd.

[0066] Rock wool felt: size is 15cm long × 15cm wide × 30mm thick, Hebei Huaou Energy Saving Technology Group Co., Ltd.

[0067] Example 1

[0068] A method for preparing a thermal insulation composite material comprises the following steps:

[0069] 30 g of multi-block polyurethane surfactant and 3 g of hexadecyltrimethylammonium bromide were dispersed in 167 g of water, stirred at a temperature of 30°C and a magnetic stirring speed of 500 rpm for 0.5 h to prepare a surfactant aqueous solution, then the pH of the above solution was adjusted to 6.45, 120 g of tetraethoxysilane was added, and then high-speed homogenization was performed at 15 kpm for 5 minutes, and then stirred at 500 rpm for 10 minutes, and then the glass fiber felt was completely immersed in the above emulsion. After the emulsion was completely absorbed, it was taken out and allowed to stand in a sealed environment at 80°C for 24 h, and finally dried to obtain a thermal insulation composite material.

[0070] Example 2

[0071] A method for preparing a thermal insulation composite material comprises the following steps:

[0072] 15 g of multi-block polyurethane surfactant and 1.5 g of hexadecyltrimethylammonium bromide were dispersed in 183.5 g of water, stirred at a temperature of 30° C. and a magnetic stirring speed of 500 rpm for 0.5 h to prepare a surfactant aqueous solution, then the pH of the above solution was adjusted to 6.45, 60 g of tetraethoxysilane was added, and then high-speed homogenization was performed at 15 kpm for 5 minutes, and then stirred at 500 rpm for 10 minutes, and then the glass fiber felt was completely immersed in the above emulsion. After the emulsion was completely absorbed, it was taken out and allowed to stand in a sealed environment at 80° C. for 24 h, and finally dried to obtain a thermal insulation composite material.

[0073] Example 3

[0074] A method for preparing a thermal insulation composite material comprises the following steps:

[0075] 30 g of multi-block polyurethane surfactant and 3 g of hexadecyltrimethylammonium bromide were dispersed in 167 g of water, stirred at a temperature of 30°C and a magnetic stirring speed of 500 rpm for 0.5 h to prepare a surfactant aqueous solution, then the pH of the above solution was adjusted to 6.45, 120 g of tetraethoxysilane was added, and then high-speed homogenization was performed at 15 kpm for 5 minutes, and then stirred at 500 rpm for 10 minutes, and then the pre-oxidized silk felt was completely immersed in the above emulsion. After the emulsion was completely absorbed, it was taken out and allowed to stand at 80°C in a sealed environment for 24 h, and finally dried to obtain a thermal insulation composite material.

[0076] Example 4

[0077] A method for preparing a thermal insulation composite material comprises the following steps:

[0078] 30g of multi-block polyurethane surfactant and 3g of hexadecyltrimethylammonium bromide were dispersed in 167g of water, stirred at a temperature of 30°C and a magnetic stirring speed of 500rpm for 0.5h to prepare a surfactant aqueous solution, then the pH of the above solution was adjusted to 6.45, 120g of tetraethoxysilane was added, and then high-speed homogenization was performed at 8kpm for 5 minutes, and then stirred at 500rpm for 10 minutes, and then the rock wool felt was completely immersed in the above emulsion. After the emulsion was completely absorbed, it was taken out and allowed to stand at 80°C in a sealed environment for 24h, and finally dried to obtain a thermal insulation composite material.

[0079] Example 5

[0080] A method for preparing a thermal insulation composite material is different from Example 1 only in that the diisocyanate used to prepare the multi-block polyurethane surfactant is toluene diisocyanate.

[0081] Comparative Example 1

[0082] A method for preparing a thermal insulation composite material comprises the following steps:

[0083] 31 g of multi-block polyurethane surfactant and 8 g of hexadecyltrimethylammonium bromide were dispersed in a solution of 2600 g of water and 1185 g of ethanol, and then 385 g of cyclohexane and 100 g of tetraethoxysilane were added. The mixture was stirred at 30° C. for 1 h, and then 50 mL of 27% ammonia water was added and stirred for 10 minutes. The glass fiber felt was then completely immersed in the above emulsion. After the emulsion was completely absorbed, it was taken out and allowed to stand in a sealed environment at 80° C. for 24 h, and finally dried to obtain a thermal insulation composite material.

[0084] Comparative Example 2

[0085] A method for preparing a thermal insulation composite material differs from Example 1 only in that no multi-block polyurethane surfactant is added, 33 g of hexadecyltrimethylammonium bromide is dispersed in 167 g of water, and subsequent operations are performed.

[0086] Comparative Example 3

[0087] A method for preparing a thermal insulation composite material differs from Example 1 only in that cetyltrimethylammonium bromide is not added, 33 g of a multi-block polyurethane surfactant is dispersed in 167 g of water, and subsequent operations are performed.

[0088] Comparative Example 4

[0089] A method for preparing a thermal insulation composite material comprises the following steps:

[0090] 30 g of multi-block polyurethane surfactant and 3 g of hexadecyltrimethylammonium bromide were dispersed in 167 g of water, stirred at a temperature of 30°C and a magnetic stirring speed of 500 rpm for 0.5 h to prepare a surfactant aqueous solution, then the pH of the above solution was adjusted to 6.45, 200 g of tetraethoxysilane was added, and then high-speed homogenization was performed at 15 kpm for 5 minutes, and then stirred at 500 rpm for 10 minutes, and then the glass fiber felt was completely immersed in the above emulsion. After the emulsion was completely absorbed, it was taken out and allowed to stand in a sealed environment at 80°C for 24 h, and finally dried to obtain a thermal insulation composite material.

[0091] Performance Testing

[0092] Figure 1 This is a macroscopic image of the thermal insulation composite material of Example 1. Figure 2 This is a side view of the thermal insulation composite material (left) and glass fiber mat (right) of Example 1. Figure 3 This is the SEM image of the thermal insulation composite material of Example 1. Figures 4-6 These are SEM images of the thermal insulation composite materials of Examples 2 to 5. Various parameters of the thermal insulation composite materials obtained from the Examples, Comparative Examples and commercial felt were measured using a hot disk transient flat plate method, as shown in Table 1.

[0093] Method for determining the volume concentration of hollow microspheres in emulsion: Take a certain volume of emulsion and stir it at 80°C for 24 hours. After drying, the reaction product obtains a white powder material. The tapped volume of the white powder material is measured. The volume concentration of hollow microspheres in the emulsion is the ratio of the tapped volume to the original emulsion volume.

[0094] Method for determining the silica content in thermal insulation composite materials: take a certain mass of fiber material and immerse it in the emulsion. After the emulsion is completely absorbed, take it out and let it stand in a sealed environment at 80°C for 24 hours. Finally, dry it to obtain a thermal insulation composite material. The composite material is calcined at 550°C for 3 hours. The mass difference between the obtained composite material and the original fiber material is the silica mass, from which the silica content in the thermal insulation composite material can be calculated.

[0095] It can be seen from the above images that the thermal insulation composite material with in-situ growth of hollow silica spheres has the morphology of hollow silica spheres grown on the fibers, while the unmodified glass fiber mat does not have this structure.

[0096] As can be seen from the figure, compared with Example 1, the content of hollow silica balls in Example 2 is lower, and the degree of reduction in thermal conductivity is slightly inferior to that of Example 1; Examples 3 and 4 use different inorganic thermal insulation matrices as the carriers of hollow silica balls. It can be seen from the figure that silica is relatively evenly distributed on the inorganic thermal insulation matrix.

[0097] However, the method of Comparative Example 1 could not produce a thermal insulation composite material. Given the hydrophilic surface of the glass fiber mat, the addition of cyclohexane prevented the latex particles from adhering to the fibers, thus preventing the formation of a thermal insulation composite material. The addition of a large amount of solvent caused the glass fiber mat to agglomerate, resulting in a decrease in porosity.

[0098] The thermal insulation composite material could not be prepared using the method of Comparative Example 2. The phase behavior of hexadecyltrimethylammonium bromide and tetraethoxysilane in water only formed solid spheres, and could not synthesize hollow spheres, thus failing to form a thermal insulation composite material.

[0099] The thermal conductivity of the thermal insulation composite material prepared by the method of Comparative Example 3 is higher. If hexadecyltrimethylammonium bromide is not added, the adhesion of the hollow spheres is higher, thereby making the thermal conductivity of the thermal insulation composite material higher.

[0100] Table 1 Technical parameters of hollow microsphere emulsions and thermal conductivity of thermal insulation composite materials of Examples 1 to 5

[0101]

[0102]

[0103] The above embodiments are preferred experimental methods of the present invention, but the implementation methods of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be considered equivalent replacement methods and are included in the scope of protection of the present invention.

Claims

1. A method for preparing a thermal insulation composite material using hollow silica balls as fillers, characterized in that: The steps include: Alkoxysilane and a surfactant aqueous solution are made to form a uniform emulsion, the inorganic thermal insulation matrix is ​​made to absorb the emulsion, and the solvent is removed after gelation to obtain the thermal insulation composite material; The surfactant aqueous solution is an aqueous solution containing a multi-block polyurethane surfactant and a cationic surfactant; The volume concentration of the hollow microspheres in the emulsion is ≥60%.

2. The preparation method according to claim 1, characterized in that: The alkoxysilane is selected from at least one of tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetrabutoxysilane, methyltrimethoxysilane, phenyltrimethoxysilane, octyltrimethoxysilane, methyltriethoxysilane, phenyltriethoxysilane and octyltriethoxysilane.

3. The preparation method according to claim 1, characterized in that: The method of forming a uniform emulsion of the alkoxysilane and the aqueous surfactant solution includes homogenization.

4. The preparation method according to claim 1, characterized in that: The gelation time is 12-72 hours.

5. The preparation method according to claim 1, characterized in that: The gelation temperature is 20-100°C.

6. The preparation method according to claim 1, characterized in that: The inorganic heat-insulating matrix is ​​selected from at least one of glass felt, rock wool or pre-oxidized fiber felt.

7. The thermal insulation composite material prepared by the preparation method according to any one of claims 1 to 6.

8. The thermal insulation composite material according to claim 7, characterized in that: The content of hollow silicon dioxide balls in the thermal insulation composite material is 10wt% to 30wt%.

9. The thermal insulation composite material according to claim 7, characterized in that: The thermal conductivity of the thermal insulation composite material is 0.030-0.05 W / (m·K).

10. Use of the thermal insulation composite material according to any one of claims 7 to 9 in the preparation of building thermal insulation and energy-saving materials, vehicle thermal insulation materials, new energy battery thermal insulation and fireproof materials, industrial pipe network thermal insulation materials or chemical equipment thermal insulation materials.

Citation Information

Cited By

  • Heat preservation and insulation rock wool board for building external wall and preparation method of heat preservation and insulation rock wool board

    CN121800463A